The Health Education with a Peer Group Support Approach in using Personal Protective Equipment (PPE) to prevent Upper Respiratory Tract Infections: Pendidikan Kesehatan dengan Pendekatan Peer Group Support dalam penggunaan Alat Pelindung Diri (APD) sebagai Upaya pencegahan Infeksi Saluran Pernafasan Atas (JURNAL UNEJ, 2023)
Upper Respiratory Tract Infections have effects that can cause sufferers to experience discomfort in the respiratory tract area. This disease can be caused by several things, including the lack of optimal use of personal protective equipment when working. This service aims to increase understanding and knowledge of using Personal Protective Equipment when working. The activities include preparing existing equipment and Personal Protective Equipment suitable for furniture factory workers. After that, provide information and knowledge to the audience regarding the impact and importance of using Personal Protective Equipment (PPE). Furthermore, a cadre was formed to supervise the use of PPE to provide support and remind each other when working. Workers with lengthy experience working can understand how working in a furniture area with dust and wood chips can be a health risk. The hope is that furniture workers will gain new motivation and enthusiasm for working using PPE by supporting each other. Furniture workers participating in this program are very active and enthusiastic in implementing this activity. Discussions with a supportive approach from peers who encourage each other to use PPE can increase enthusiasm in daily work in the workplace or on furniture